(untitled) (Proceedings of Voronezh State University. Series: Geology, 2021)
Introduction: Zeolites are the best adsorbents, and for this reason they attract close researcher’s attention. At the same time, they are widely used in various industrial sectors and agriculture, and over time the areas of their application constantly expand. The industrial value of zeolites is mainly determined by their unique ion-molecular sieve, and catalytical properties associated with the crystallochemical peculiarities of zeolites, their ability for cation exchange as well as loss and absorption of water and other molecules without the destruction of the structural framework. Natural zeolites, such as clinoptilolite and mordenite, are especially significant. Their comprehensive study is required due to the expansion of the industrial opportunities to utilize the zeolites of Azerbaijan, where large deposits of zeolite-containing tuffs are favourably situated (Aydag, Agdag, Yukhary Oksyuzli, Tatly, Tug, Talysh deposits, etc.). Methodology: To study the composition of zeolites from various deposits, were conducted more than 50 chemical analyses of zeolitised tuffs and performed the mineralogical analysis of the smallest fractions of clinoptilolite tuffs. The refraction index of the micro-flaked aggregate of clinoptilolite was determined and the amount of minerals was calculated, the diffraction data of zeolites were obtained at room temperature on a DRON-3 diffractometer (CuKα radiation, Ni filter, 30 kV, 20–26 mA, counter speed 0.50 θ/min.). Results and discussions: The article analyses the current state of study and some peculiarities of natural zeolites of Azerbaijan with various mineral and chemical compositions. According to the results of chemical analyses, we found that the composition of the minerals from the zeolite group and zeolitised tuffs of the Kazakh trough is characterised by a high content of silica, the predominance of iron oxide over ferrous iron as well as the predominance of calcium over magnesium and sodium over potassium. It was established that the magmatic zeolite is represented by analcime which is located in the form of xenomorphic segregations in the interstice of early rock-forming minerals, such as olivine, clinopyroxene, plagioclase, biotite, hornblende, and others, as part of the teschenites of the Tugh and Kalakhan intrusions. The next genetic type of zeolites is analcime that was formed as a result of the metasomatic transformation of high-temperature leucite. Further, the conditions for the formation of hydrothermal and sedimentary-diagenetic zeolites were studied. It was found that high-silica zeolites (clinoptilolites and mordenites), which are of industrial value, had been formed as a result of hydration of acidic hyaloclastites with a thedacite-rhyodacite composition. Conclusions. It was established that in most cases ash tuffs of trachyandesibasalts, andesites, dacites, and rhyodacites are the initial material for the formation of zeolites. The diversity in the compositions of the products of the explosive activity of Late Cretaceous and Cenozoic volcanism is associated not only with the conditions of the tectonic and magmatic mode, although it is one of the critical factors in the formation of analcime and clinoptilolite-mordenite deposits.